Comparing applicants and incumbents: Effects of response distortion on mean scores and validity of personality measures. (September 2017) - Jeong, Ye Ra; Christiansen, Neil D.; Robie, Chet; Kung, Mei‐Chuan; Kinney, Ted B.
Abstract : This study examined the negative effect of likely applicant distortion on mean scores and validity of personality measures. The personality test scores and performance ratings of applicants were directly compared to those of incumbents with the same occupation in four different samples. The results showed that applicant mean scores were higher and validity coefficients were lower than for incumbents.